ADSORPTION OF AN NH3 MOLECULE ON Cr(111) SURFACE BY QCMP 116 PROGRAM - Charles Banon (Indonesian Journal of Chemistry, 2010)
Interactions of an NH3 molecule on chromium (111) surface consists of 20 atoms with three layers has been studied by QCMP 116 (Calzaferri) program, run on IBM PC compatible (Pentium III, 660 MHz). An oncoming NH3 (with the planar molecular plane parallel or perpendicular to surface), at many positions, was optimized three dimensionally by that program. Observing the binding energy of an NH3 on surface (BE (NH3)) and inter atomic distances at the optimized conditions. It's showed that:  an oncoming NH3 molecule, with molecular plane parallel to the surface, N atom was oriented to atoms of the first and third layer. One of its NH bond was parallel to the Cr-Cr bond were chemisorbed molecularly with BE(NH3) in range of 0.9797-1.3421 eV/molecule. On the second layer was chemisorbed atomically. However, an oncoming NH3 with molecular plane perpendicular to the surface (with N atom and one of its N-H bond perpendicular to Cr atom) was adsorbed physically with BE(NH3) in a range of 0.4903-0.5614 eV/molecule.